Oral Health Knowledge, Attitude, and Behavior of Nursing and Technical Students in Croatia - Cabov, Tomislav; Eljuga, Ksenija; Fuchs, Petra Nola; Devcic, Maja Kinkela; Prpic, Jelena; Kovac, Zoran; Puharic, Zrinka; Glazar, Irena; Zulec, Mirna (European Journal of Dentistry, 2021)
Objective The aim of this study was to test knowledge, attitudes, and behavior of the students from the Bjelovar University of Applied Sciences in relation to oral health, and to determine the respectable differences between students of nursing and technical study programs.Materials and Methods Students were randomly selected to represent a convenient sample. A total of 140 students from nursing and technical studies were interviewed by using the World health organization Oral Health Questionnaire, adapted to fit the study purposes.Statistical Analysis Descriptive statistics were used to determine frequency distribution and percentages for all variables. Pearson’s Chi-square test was used to compare the proportions. A p-value less than 0.05 was considered to be statistically significant.Results The distribution of participants regarding gender was significantly different between the study programs (p = 0.000). Significant difference was also observed in their perceived socioeconomic status (p = 0.001). A significant difference was found between the study programs regarding the knowledge whether bad teeth could impair general health (p = 0.001), could tooth decay and periodontal disease may be prevented (p = 0.002), as well as the importance of regular dental check-ups for prevention of tooth decay (p = 0.028). There were significant differences regarding dietary habits and alcohol consumption in the past 30 days between the observed study programs (p = 0.000) while no significant differences were found regarding tobacco and tobacco product use (p = 0.170).Conclusion Results obtained and presented in this paper show better knowledge and more favorable habits and behaviors among the students from nursing study program compared with the technical ones. Still all students’ habits should be changed to improve oral health. To change attitudes and influence habits, effective oral health promotion programs are needed; not only in colleges, but also in primary and secondary schools.
Keywords: attitude; habits; knowledge; oral health